Validation of the alcohol use disorders identification test (AUDIT) – Bahasa Malaysia version among a group of alcohol users - Yee, A.; Adlan, A.S.; Rashid, R.A.; Habil, H.; Kamali, K. (Taylor & Francis, 2015)
Background: The Alcohol Use Disorder Identification Test (AUDIT) developed by the WHO is designed to identify individuals along the full spectrum of alcohol misuse. This study aimed to develop and validate a Bahasa Malaysia language version (AUDIT-M) of the AUDIT. Methods: AUDIT was translated to Bahasa and back translated to English. The first version was pilot tested. The final version was administered to all the patients who were identified as alcohol users from the outpatient psychiatric clinic, or were admitted to the psychiatric ward of the University Malaya Medical Centre. Patients completed a demographic questionnaire, English and Bahasa Malaysia versions of AUDIT, M.I.N.I., CAGE, and the Bahasa Malaysia version of the WHOQoL-Bref-M. Results: Factor analysis of AUDIT-M yielded two factors similar to the factor structure of the English version. The Cronbach α coefficients for the total AUDIT-M was 0.823; and 0.816 and 0.68 for the two AUDIT-M factors. There was a significant correlation between the AUDIT and AUDIT-M scores (Spearman's ρ=0.979, p<0.01). The test-retest reliability coefficient was also high (Spearman's ρ=0.955, p<0.01). The total AUDIT-M had a significant positive correlated with the CAGE (p<0.01) and inversely correlated with the four subscales of WHOQoL-Bref-M. Conclusion: The AUDIT-M questionnaire has acceptable psychometric properties and is suitable for the assessment and identification of AUD in Malaysia.